Challenges in Microfluidic and Point-of-Care Phenotypic Antimicrobial Resistance Tests - Needs, Sarah H.; Donmez, Sultan I.; Bull, Stephanie P.; McQuaid, Conor; Osborn, Helen M. I.; Edwards, Alexander D. (Frontiers in Mechanical Engineering, 2020)
To combat the threat to public health of antimicrobial resistance, there is a need for faster, more portable diagnostic tools to aid in antibiotic selection. Current methods for determining antimicrobial resistance of pathogens in clinical samples take days to result and require high levels of user input. Microfluidics offers many potential benefits, reducing time to result, user input and allowing point of care testing. This review focuses on the challenges of developing functional or phenotypic microfluidic antimicrobial susceptibility tests; such methods complement other vital tools such as nucleic acid detection. Some of the most important challenges identified here are not unique to microfluidics but apply to most antimicrobial susceptibility testing innovations and relate to the nature of the sample being tested. For many high priority samples, mixtures of bacteria, highly variable target cell density, and the sample matrix can all affect measurements, and miniaturisation can create sensitivity problems if target bacteria are dilute. Recent advances including smartphone capability, new sensors, microscopy and a resurgence in paper microfluidics offer important opportunities for microfluidic engineering to simplify functional and phenotypic antimicrobial susceptibility testing. But the complexity of most clinical samples remains one of the biggest barriers to rapid uptake of microfluidics for antimicrobial resistance testing.